Dermatopathologists’ Experience With and Perceptions of Patient Online Access to Pathologic Test Result Reports - Shucard, Hannah (JAMA Dermatol, 2020)
IMPORTANCE: Many patients presently have access to their pathologic test result reports via online patient portals, yet little is known about pathologists’ perspective on this topic. OBJECTIVE: To examine dermatopathologists’ experience and perceptions of patient online access to pathology reports. DESIGN, SETTING, AND PARTICIPANTS: A survey of 160 dermatopathologists currently practicing in the United States who are board certified and/or fellowship trained in dermatopathology was conducted between July 15, 2018, and September 23, 2019. Those who reported interpreting skin biopsies of melanocytic lesions within the previous year and expected to continue interpreting them for the next 2 years were included. MAIN OUTCOMES AND MEASURES: Dermatopathologists’ demographic and clinical characteristics, experiences with patient online access to pathologic test result reports, potential behaviors and reactions to patient online access to those reports, and effects on patients who read their pathologic test result reports online. RESULTS: Of the 160 participating dermatopathologists from the 226 eligible for participation (71% response rate), 107 were men (67%); mean (SD) age was 49 (9.7) years (range, 34-77 years). Ninety-one participants (57%) reported that patients have contacted them directly about pathologic test reports they had written. Some participants noted that they would decrease their use of abbreviations and/or specialized terminology (57 [36%]), change the way they describe lesions suspicious for cancer (29 [18%]), and need specialized training in communicating with patients (39 [24%]) if patients were reading their reports. Most respondents perceived that patient understanding would increase (97 [61%]) and the quality of patient-physician communication would increase (98 [61%]) owing to the availability of online reports. Slightly higher proportions perceived increased patient worry (114 [71%]) and confusion (116 [73%]). However, on balance, most participants (114 [71%]) agreed that making pathologic test result reports available to patients online is a good idea. CONCLUSIONS AND RELEVANCE: Dermatopathologists in this survey study perceived both positive and negative consequences of patient online access to pathologic test result reports written by the respondents. Most participants believe that making pathologic test result reports available to patients online is a good idea; however, they also report concerns about patient worry and confusion increasing as a result. Further research regarding best practices and the effect on both patients and clinicians is warranted.